O estado da arte das políticas de formação inicial de professores para a educação básica no Brasil no período de 2004 a 2014 - Espíndula, Júlia Maccari (2017)
The present dissertation aims to present the State of the Art on initial teacher education policies for Basic Education in Master's dissertations in the area of Education from 2004 to 2014 in Brazil. The themes of these surveys are analyzed in relation to the educational policies of education in force from the Law of Guidelines and Bases of National Education, Law 9.394/96. The objective was to identify the themes and objectives of Master dissertations defended in the above mentioned period from the LDB / 96, from a materialist dialectical bias. It was evaluated how much the research followed the political propositions of the field of teacher training, as well as the subjects and objects of study of them. The methodology of the research consisted of searching the databases of theses and dissertations of CAPES and IBICT research that fit the intended scope. The first search, which occurred through nine seekers, was made in the CAPES theses and dissertations bank in September 2015, but it was not efficient. The CAPES website was under renovation and only the 2011 and 2012 surveys were available for consultation. The BDTD (Theses and Dissertations Bank) website was then chosen for research bank and through it 2,588 theses and dissertations were found through seven keywords (Training Policy, Teacher Training, LDB Training, Teacher Training, Training For the Basic Education, National Curricular Guidelines for Teacher Training and National Curricular Guidelines and Training). After analyzing the 2,588 researches, only 32 MSc dissertations fit within the intended cut. The first research was on the theme of these dissertations and their relationship with initial teacher education policies. After careful reading, the 32 dissertations were classified into four categories: Curriculum, Distance Education, Training and Work Policy, and Initial Training Policy and Teaching Work. Another aspect verified was the geographic region in which the PPGEs in which the dissertations were developed were located. 91% of the bibliographic publication analyzed in this work was produced in the South and Southeast regions and in the North region no relevant production for this research was produced. The nature (public, private, community, etc.) of the Higher Education Institutions in which these researches were developed were also analyzed, as well as the regions of the country in which they are located. The initial teacher training was discussed within this work since its beginning in Brazil, going through political and locus changes throughout history. Besides the historical approach, there is a political reflection on the implications of teacher education and the laws and guidelines that legitimize it. The predominant theme, present in 50% of the dissertations, was related to the teaching work, which discusses the implications of precarious teacher training in classroom work. The study concluded that, although there is a representative academic production on initial training policies in the proposed period, some topics are likely to be further developed, such as education by distance and the curriculum of initial training.